2014
DOI: 10.5507/bp.2013.071
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of effective dose and organ dose to the eye lens in head MDCT using iterative image reconstruction and automatic tube current modulation

Abstract: Aims.To compare the effective and eye lens radiation dose in helical MDCT brain examinations using automatic tube current modulation in conjunction with either standard filtered back projection (FBP) technique or iterative reconstruction in image space (IRIS). Methods. Of 400 adult brain MDCT examinations, 200 were performed using FBP and 200 using IRIS with the following parameters: tube voltage 120 kV, rotation period 1 second, pitch factor 0.55, automatic tube current modulation in both transverse and longi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
(53 reference statements)
0
5
0
Order By: Relevance
“…More recently, reductions in global tube current, without significant compromises in image quality, have become more feasible following the introduction of more effecient iterative reconstruction methods. In a clinical trial, Ryska et al observed an overall 33% decrease in average effective dose with such techniques, with an ensuing 33% decrease in dose detected at the eyes. Other studies have also demonstrated potential reductions in effective dose with the use of iterative reconstruction; however, direct inferences regarding any reductions in dose to the lenses of the eyes were not specified in these cases.…”
Section: Radiation Reduction Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, reductions in global tube current, without significant compromises in image quality, have become more feasible following the introduction of more effecient iterative reconstruction methods. In a clinical trial, Ryska et al observed an overall 33% decrease in average effective dose with such techniques, with an ensuing 33% decrease in dose detected at the eyes. Other studies have also demonstrated potential reductions in effective dose with the use of iterative reconstruction; however, direct inferences regarding any reductions in dose to the lenses of the eyes were not specified in these cases.…”
Section: Radiation Reduction Strategiesmentioning
confidence: 99%
“…Despite continuous endeavours in technological advances and awareness in regards to radiation safety, it has been purported that the average medically induced radiation dose per capita is increasing, particularly in well‐developed countries. For the most part, this upward trend can likely be attributed to the exponentially increasing demand for CT scans, which contributes to approximately one half of the overall effective radiation dose from medical procedures per capita in the United States …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the year 2018 the number of CT scans in Sweden was 1.5 million, an increase of 130% compared to 2005 [3]. Over time, technological advances and awareness of radiation protection has led to lowered doses to the head in diagnostic CT scans, but the comparably high doses of ionizing radiation from CT remain a concern, especially since the number of scans continue to increase [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Some recent previous work examples related to radiation protection for radiosensitive organs during CT examination such as eye and thyroid gland are illustrated as follows. "Pavel Ryska et al concluded that Iterative reconstruction of cerebral Multi Detector CT (MDCT) examinations enables reduction of both effective and organ eye lens dose by one third without significant loss of image quality [5]. Huda et al, reported that thyroid doses can be estimated by taking into account the amount of radiation used to perform the CT examination (CTDI(vol)) and accounting for scan length and patient anatomy (i.e., neck diameter) at the thyroid location [6].…”
Section: Introductionmentioning
confidence: 99%